SURVEILLANCE AND POWER IN THE CLASSROOM: THE INFLUENCES OF THE PANOPTICON IN THE FOREIGN LANGUAGE TEACHING ENVIRONMENT - Severian, Marina Rosa [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
Schools are generally considered panopticons, since they allow, through their architectures, surveillance of both learners and teachers. It is believed that this control, supposedly uninterrupted may trigger different effects of power in the relationship between these subjects. In order to look at the influences of panoptic theory in foreign language classrooms, we rely on the Benthanian and Foucaultian theory of the concept of panopticon to discuss how power and surveillance can be established in two distinct scenarios of classroom. Based on these scenarios, we believe that the physical structure of the classroom can be a determining factor to intensely or subtly maintain the effects of power through surveillance.
Keywords: Foreign language teaching; Scholar panopticon; Surveillance; Power